Irisin Level in Salah Adin’s Insulin Resistance Syndrome Patients in View of Global Controversy - Sedeem Zeki Salih, Sami A Zbaar, Mohamed Ghalib Zakari (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Metabolic syndrome (high blood pressure, hyperglycemia, dyslipidemia, and obesity) is now an international health problem that impacts about 20 per cent to 25 per cent of the total population and can be worsened in the developing world, particularly in the Middle East, which is roughly two out of every five Iraqis. The metabolic syndrome has a direct link to many life-threatening diseases, such as cardiovascular disease, early onset of some cancers, such as colorectal cancer, Chronic liver illnesses, polycystic ovarian syndrome, and others. Methodology: A case-control study on a total of ninety volunteers (46 males and 44 females), comprising sixty metabolic syndrome patients (25 males and 35 females), defined in terms of international diabetic federation criteria, and thirty controls, is to be conducted at Salah Alden general hospital. Adults men and women aged (24-to 65) years who attended Salah Alden’s main hospital outpatient clinics in Tikrit, from October 2021 to March 2022 were included in the research. The levels (Irisin, and Insulin) in all research groups and controls are evaluated using an Enzyme-Linked Immune-sorbent Assay. Results: Irisin level was significantly higher among controls with a mean of (6.84ng/ml), compared to metabolic syndrome patient mean (5.71 ng/ml), and significantly negatively correlated to triglycerides level, and non-significantly negatively correlated with (systolic blood pressure, fasting serum glucose, and waist circumference) and non-significantly positively correlated to high-density lipoprotein level. Irisin levels were significantly different among treatment-based groups with the highest mean level among the treatment-free group (6.8450ng/ml±1.96052), followed by the antihypertensives taking group (5.3340ng/ml±2.99273), and the lowest mean level was recorded among diabetics (4.8916ng/ml±2.81952). Conclusion: With the exception of HDL, a high level of Asprosin and a low level of Irisin are strongly linked to metabolic syndrome and its components. Irisin levels differ amongst metabolic syndrome patients with various therapy groups. Keywords: Irisin, metabolic syndrome, Insulin Resistance.